Effect of Service Quality on Customer Satisfaction of Domestic Airlines in Nepal (Quest Journal of Management and Social Sciences, 2020)
Background: Airlines industries have great share in economic growth, tourism, world trade and international investment in today's globalized business world. Due to this purpose the attraction towards airlines companies seems to be increasing which have forced them to maintain certain quality level in order to compete and sustain in long run.Objective: This paper aims to analyze the affect of service quality on customer satisfaction of domestic airlines in Nepal along with identification of customer perceived service quality in the aviation business and to examine factors influencing passenger's satisfaction in the aviation business.Methods: Regression is used for generating effective output of the study. Likewise, ANOVA test, reliability test are also performed with the help of statistical tools.Results: Customers are satisfied if employees behave well with them and airlines value them with proper services and information. Also, the study reveals that there is significant relationship between customer satisfaction and tangibility, reliability, responsiveness, empathy and assurance.Conclusions: The most influencing factors in selection of airlines is security they assures and timely flights so, if airlines companies took these things into consideration then it would help in increasing customer satisfaction.Originality: This paper is original and not sent for publication anywhere else.